A comparative study on single- and double-arc deposition processes. Issue 3 (17th February 2020) - Wu, Wei; Xue, Jiaxiang; Yao, Ping
ABSTRACT: Arc additive manufacturing based on gas metal arc welding (GMAW) can decrease the cost and increase the efficiency of manufacturing large-sized components. In this paper, a double-arc additive manufacturing process for stainless steel 316L (SS316L) based on GMAW that does not use more power than the single-arc process is proposed. In addition, this study compared single- and double-arc additive manufacturing processes by analyzing the morphology, microstructure, and mechanical properties. The results indicate that with the same power, the deposition rate of the double-arc process was 1.25 times higher than that of the single-arc process. Further, the increased number of welding wires and the induced stirring of the molten pool produced finer grains. In addition, the average Vickers hardness and tensile strength of the double-arc sample were 0.6% and 3.5% higher than those of the single-arc samples, respectively, while the elongation was 0.34% lower, and the tensile properties had a similarity of over 90% with those of the SS316L wire.